Encephalopathy following melphalan administration. (2nd January 2017) - Dubey, Divyanshu; Freeman, Matthew; Neeley, Om James; Carter, Gregory
Abstract : Objective:: To describe a rare case of encephalopathy following melphalan administration. Presentation and intervention:: A 59-year-old female with multiple myeloma developed encephalopathy following administration of melphalan. After ruling out other aetiologies, we hypothesized elevated cytokines from systemic inflammatory response to melphalan as the likely aetiology. The TNF-alpha level was found to be significantly elevated. Plasmapharesis was performed which reduced the level of cytokines, and also improved the patient's neurological status. Conclusion:: Melphalan administration, especially in renally impaired patients, may lead to development of encephalopathy. Based on our case report, we suggest that elevated levels of cytokines could be the underlying mechanism of worsening mental status.